Change in Lung Function over Time in Male Metropolitan Firefighters and General Population Controls: A 3‐year Follow‐up Study. Issue 4 (6th February 2014) - Schermer, Tjard R.; Malbon, Winifred; Adams, Robert; Morgan, Michael; Smith, Michael; Crockett, Alan J.
Abstract : Change in Lung Function over Time in Male Metropolitan Firefighters and General Population Controls: A 3‐year Follow‐up Study: Tjard R. SCHERMER, et al. Discipline of General Practice, School of Population Health, The University of Adelaide, Australia Objective: Previous studies in firefighters have been contradictory regarding their course of lung function over time. The aim of this ongoing study is to investigate how changes in lung function over time in male metropolitan firefighters compare with those in population controls, and to explore associations between firefightersï¿½ use of personal respiratory protection devices during occupational exposures and their risk of accelerated lung function decline. Methods: A prospective comparison of FEV1 (forced expiratory volume in 1 second) and FVC (forced vital capacity) was performed between 281 firefighters and 933 population controls. Logistic regression models were used to compare changes from baseline of FEV1 and FVC after 3 years and risk of accelerated decline between the cohorts. Within the firefighter cohort, risk of accelerated decline was compared between subgroups based on use of respiratory protection devices. Results: Controls showed similar mean annual declines for FEV1 and FVC across age categories, whereas firefighters aged <45 years showed increasing values over time (p=0.040). Firefighters had a lower odds of accelerated FEV1 decline compared with controls (OR=0.60, 95%CI 0.44; 0.83), but firefighters who never or rarely used respiratory protection during fire knockdown had a higher odds of accelerated FEV1 decline compared with those who used it often or frequently (OR=2.20, 95%CI 1.02; 4.74). Conclusions: Younger generations of firefighters showed an increase in lung function relative to older colleagues, while population controls consistently showed decline of lung function across all ages. Firefighters who reported to be incompliant in using respiratory protection showed an increased risk of accelerated FEV1 decline.